2016
DOI: 10.1088/0964-1726/25/8/084008
|View full text |Cite
|
Sign up to set email alerts
|

A bacteria-based bead for possible self-healing marine concrete applications

Abstract: This work presents a bacteria-based bead for potential self-healing concrete applications in low-temperature marine environments. The bead consisting of calcium alginate encapsulated bacterial spores and mineral precursor compounds was assessed for: oxygen consumption, swelling, and its ability to form a biocomposite in a simulative marine concrete crack solution (SMCCS) at 8 °C. After six days immersion in the SMCCS the bacteria-based beads formed a calcite crust on their surface and calcite inclusions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 34 publications
(56 reference statements)
4
47
0
4
Order By: Relevance
“…Jonkers et al developed since 2006 in a series of studies a bacterial spore and an organic compound–based healing agent for providing autonomous healing potential to concrete under aerobic conditions (see and references therein, and). The specific healing agent contains organic compounds in the form of calcium salts of fatty acids such as calcium formate, calcium acetate, calcium glutamate, calcium propionate, and calcium lactate or lactate derivatives .…”
Section: Self‐healing Bioconcretementioning
confidence: 99%
See 1 more Smart Citation
“…Jonkers et al developed since 2006 in a series of studies a bacterial spore and an organic compound–based healing agent for providing autonomous healing potential to concrete under aerobic conditions (see and references therein, and). The specific healing agent contains organic compounds in the form of calcium salts of fatty acids such as calcium formate, calcium acetate, calcium glutamate, calcium propionate, and calcium lactate or lactate derivatives .…”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…Wang et al have also considered a modified‐alginate biohydrogel containing around 4 × 10 9 spores g −1 of hydrogel . Palin et al applied alginate beads to encapsulate spores of an undisclosed bacterium . The beads consisted of calcium alginate and mineral precursors and were produced by pumping dropwise a precursor solution of magnesium acetate, yeast extract, and 7 × 10 8 of unidentified bacteria spores per liter into a calcium acetate solution.…”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…This method has not been investigated for the production of microcapsules for construction and structural applications. However, recently some preliminary studies reported the use of alginate to encapsulate corrosion inhibitors [10] and bacteria for selfhealing concrete [23][24][25].…”
Section: +mentioning
confidence: 99%
“…Jonkers and co‐workers were among the first to apply the oxidation of organics based on bacteria in concrete and to further propose the idea of self‐healing concrete by relying on bacteria‐mediated CaCO 3 precipitation . Typical spore‐forming alkaliphilic strains, including Bacillus cohnii , Bacillus pseudofirmus , and Bacillus alkalinitrilicus , were used.…”
Section: Mechanisms Of Intrinsic Self‐healing: Guest–host Interactionsmentioning
confidence: 99%